When beauty tamed the beast - James, Eloisa (Piatkus, 2012)
If only Miss Lisle Berry Thynne's gown hadn't been so fully cut, or she hadn't been caught kissing that prince ... But now the ton believes Lisle to be with royal child - and therefore unmarriageable - so she might as well make her desperate father happy by consenting to wed a beast. A brilliant surgeon with a reputation for losing his temper - and a wound believed to have left him ... incapable - Piers, Earl of Montague, should welcome a bride-to-be carrying a ready-made, blue-blooded heir. But Piers isn't fooled by the lady's subterfuge, and though Lisle's devilishly smart and charming with a loveliness that outshines the sun, there will be no wedding of beauty to beast.